Sonnets of Louise Labé "La Belle Cordière." - Labé, Louise, approximately 1526-1566 (University of Toronto Press, 1950)
With Labé's poems, the translator presents a sketch of the circumstances and background of this unique literary figure of the Sixteenth Century, known in France and outside of France asLa Belle Cordière.